Measurement in Worship and Examples of Its Jurisprudential Applications - Ayed , Akram (Islamic Sciences Journal, 2023)
The science of the fundamentals of jurisprudence is one of the necessary sciences, as it is the basis on which jurisprudential rulings are built, and from this accurate science many sciences branch out, including analogy. Islamic law, as it deals with new issues and events in all areas of life, and the importance of measurement in worship is of great importance because it relates to knowing the extent of the legitimacy of analogy in worship, and the reader of Islamic schools finds a great disagreement in their sayings, some of them deny it and some of them allow it, so the study aims to address this topic To achieve this goal, the researcher used the analytical inductive method, and in this research a new addition in the field of studies related to the principles of jurisprudence, and the study concluded with the most important results, including that analogy is a legitimate argument to prove judgments, which is the fourth evidence of judgments, and this is the opinion of the public, the permissibility of analogy in acts of worship with reasonable meaning. That is, whatever the cause is known, and as for acts of worship whose meaning is unknown, it is not permissible to measure them, such as measuring the night fast over the day, and this is what the majority of scholars went to.